Analisis Kemampuan Backhand Drive Tenis Meja Mahasiswa Olahraga - Sari, Dessi Novita (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2025)
This research aims to determine the ability of table tennis backhand drive skills of students at the Faculty of Sports Science, Padang State University in an effort to overcome students' low basic technical skills during practical table tennis lectures. The research carried out was descriptive research, data analysis techniques using descriptive statistics using frequency tabulation with percentage calculations. The population in this study was 20 FIK students taking table tennis courses. Samples were drawn using a total sampling technique. The data collection technique uses a test backboard. The research results showed that there were 2 people (10%) with a very good classification, 4 people (20%) with a good classification, 6 people (30%) with a fair classification, 8 people (40%) with a poor classification and no very poor classification.